ChemInform Abstract: Synthesis of Isoindolo[1, 4]benzoxazinone and Isoindolo[1, 5]benzoxazepine: Two New Ring Systems of Pharmaceutical Interest. Issue 1 (17th December 2015) - Parrino, Barbara; Ciancimino, Cristina; Carbone, Anna; Spano, Virginia; Montalbano, Alessandra; Barraja, Paola; Cirrincione, Girolamo; Diana, Patrizia
Abstract: Product (IXa) shows promising antitumor activity against different cancer cell lines.